Situational systematicity: A role for schema in understanding the differences between abstract and concrete concepts. Issue 1 (17th February 2020) - Davis, Charles P.; Altmann, Gerry T. M.; Yee, Eiling
ABSTRACT: Abstract concepts differ from concrete concepts in several ways. Here, we focus on what we refer to as situational systematicity : The objects and relations that constitute an abstract concept (e.g., justice ) are more dispersed through space and time than are those that typically constitute a concrete concept (e.g., chair ); a larger set of objects and relations constitute an abstract concept than a concrete one; and exactly which objects and relations constitute a concept is more context-dependent for abstract concepts. We thus refer to abstract concepts as having low situational systematicity. We contend that situational systematicity, rather than abstractness per se, is a critical determinant of the cognitive, behavioural, and neural phenomena associated with concepts. Further, viewing concepts as schema provides insight into (i) the situation-based dynamics of concept learning and representation and (ii) the functional significance of the brain regions and their interactions that comprise the schema control network .